Human Vascular Endothelial Cells Catabolise Exogenous Glycosaminoglycans by a Novel Route - Dawes, Joan; Pepper, Duncan S (Thrombosis and Haemostasis, 1992)
Heparin and other anticoagulant glycosaminoglycans were radiolabelled with 125I and their catabolism by human vascular endothelial cells in culture was studied. Heparin, heparan sulphate and pentosan polysulphate were associated with the cellular fraction and incorporated into the subendothelial matrix, but dermatan sulphate was not found in either fraction. High molecular weight, fully desulphated carbohydrate chains were major catabolic products of all those glycosaminoglycans which were taken up by the cells. Pentosan polysulphate was not degraded further, but the catabolism of heparan sulphate, and to a lesser extent that of heparin, also yielded small oligosaccharides. Thus the first step in catabolism of exogenous glycosaminoglycans by human vascular endothelial cells appears to be complete desul-phation, which destroys their biological activity, followed by depolymerisation of the carbohydrate chain. This alternative to the sequential action of lysosomal exoenzymes is dependent upon binding to the cell; thus dermatan sulphate, which is not associated with the cellular fraction, is not catabolised.